Endovascular Treatment for Pseudoaneurysms after Surgical Correction of Aortic Coarctation. (7th March 2011) - Rabellino, M.; Zander, T.; González, G.; Baldi, S.; Cheves, H.; Estigarribia, A.; Llorens, R.; Carreira, J. M.; Maynar, M.
Abstract : Late complications after surgical repair of aortic coarctation are not uncommon. Among these complications pseudoaneurysms are the most frequent complications, occurring between 3 and 38%. Reoperation in these patients is associated with high morbidity and mortality. In the last decade, endovascular techniques emerged as an alternative to conventional surgery with excellent results. We report the case of two patients who presented with pseudoaneurysms after surgical correction for aortic coarctation, which were treated by endovascular means.